(untitled) (Journal of Hama University, 2019)
Endodontic treatment is affected differentially by fractured instrument, according to several variables such as separation locus in root canal. Secondary Procedural errors increase during fractured instrument retrieval attempts especially in apical region of root canal. This study aims to investigate effects of some variables contributing positively in organism support to retain of Apical Fractured Instrument (AFI). This study consists of retrospective clinical and radiological part distributed into 4 groups (n=10) with AFI: before or after root canal preparation then obturated by using modified single cone or thermal vertical condensing techniques. Clinical symptoms and radiological signs were followed up during 1 year, 3 year, 6 year. Variables of clinical part were mimicked by using in vitro groups (n=10) in order to observe stain microleakage into root canal apex, linked to apical sealing affected. Proper negative and positives controls were used. Statistical Analysis (P<0.05) show non-significant differences between studied groups during periods of follow-up clinically and radiologically. Post-preparation AFI Group obturated using thermal vertical condensing shows the best prognosis, versus the worst one for the pre-preparation AFI, obturated using modified single cone. In Vitro, significant differences regarding apical stain microleakage were found regarding Post-preparation AFI Group, obturated using thermal vertical condensing, versus other groups. We conclude that AFI, non-responding to retrieval or bypass attempts, don’t result in necessarily endodontic treatment failure. Good prognosis of AFI linked to bacterial microleakage prevention, and the obturation technique of choice is thermal vertical condensation.